Introduction of 1-m MSBS in Tohoku University, new device for aerodynamics measurements of the sports equipment - Okuizumi, H.; Sawada, H.; Nagaike, H.; Konishi, Y.; Obayashi, S. (Proceedings, 2018)
Support interference in wind tunnel testing is an unavoidable effect. It is difficult to measure the aerodynamic force acting on a model such as a ball owing to this effect [1]. A magnetic suspension and balance system (MSBS) suspends the model without any mechanical supports by using magnetic force, and at the same time, can measure the aerodynamic force acting on the model. The 1-m MSBS, located at the Institute of Fluid Science, Tohoku University, is the world`s largest MSBS. It has a 1-m-wide octagonal cross section. A sphere is taken as the experimental object, and the results of the aerodynamic force acting on it are presented. The diameter of the sphere is 150 mm, and its blockage ratio is 2.1%. The experiment was conducted at Reynolds numbers ranging from 0.5 × 105 to 4.7 × 105. It clearly shows the drag crisis at approximately Re = 3.7 × 105, and the fluctuation of the sphere abruptly increase around this region.